Array sites established in multiple locations in India, Southeast Asia, Latin America, and Africa - CGIAR Research Program on Rice (2018)
Partners network was key to the innovation. Sequenced Antenna panel distributed to Global Array sites, covering climate vulnerable areas. Results collected on 15 sites are being processed. Information on the impact of environmental factors on rice production was generated for Africa and Latin America using crop modelling.